On-sun testing of Miscibility Gap Alloy thermal storage. (1st January 2019) - Copus, Mark; Fraser, Benjamin; Reece, Roger; Hands, Stuart; Cuskelly, Dylan; Sugo, Heber; Reed, Samuel; Bradley, James; Post, Alexander; Kisi, Erich
Highlights: An MGA thermal storage block was used to directly absorb concentrated sunlight. Sensible and latent heat storage was demonstrated over a period of hours. The material was shown to be quite resistant to rapid changes in incident flux. The thermal conductivity was found to be 55 W/mK. Integration of solar receiver, storage and heat exchanger appears possible. Abstract: The ability of a C-Zn Miscibility Gap Alloy (MGA) material to operate as a combined solar receiver and storage was investigated. MGA thermal energy storage materials comprise metallic PCM particles embedded within a conducting metal or semi-metal matrix to form a macroscopically solid combined latent heat/sensible heat storage material. A receiver containing 4 × 1L MGA storage modules was mounted on a solar concentrating dish. The storage material was directly illuminated by concentrated solar radiation at a flux of approximately 105 kW/m 2, readily attaining surface temperatures of 520–530 °C, well above the phase change temperature of 420 °C. Single step charging led to a state of charge of 80% without exceeding a nominal surface temperature of 530 °C. Cycling on and off sun in the range 460–520 °C was used to achieve a state of 99% charged. Thermal performance of the MGA during solar charging and its discharge by natural cooling is presented and analysed.